CIRCULATING MIR-132, MIR-146A, MIR-222, AND MIR-320 EXPRESSION IN DIFFERENTIAL DIAGNOSIS OF WOMEN WITH POLYCYSTIC OVARY SYNDROME - Soyman, Z.; Durmus, S.; Ates, S.; Simsek, G.; Sozer, V; Kundaktepe, B. P.; Kurtulus, D.; Gelisgen, R.; Sal, V; Uzun, H. (EDITURA ACAD ROMANE, 2022)
Purpose. The aim of the study was to investigate whether the circulating miR-132, miR-146a, miR-222, and miR-320 levels are used in the differential diagnosis of women with polycystic ovary syndrome (PCOS) and healthy women. Methods. This prospective case-control study included 50 women with PCOS and age- and body mass index-matched 50 healthy controls. The hormone and lipid profiles, levels of microRNAs (miRNAs), and parameters of carbohydrate metabolism were measured. Results. Expression levels of miRNAs were assessed using the two-step quantitative real-time polymerase chain reaction. Circulating miR-132, miR-146a and miR-222 levels were significantly downregulated in the PCOS group compared with the control group. The miR-320 levels did not differ between the two groups. Free testosterone was negatively correlated with miR-132, miR-146a and miR-222. Insulin was negatively correlated with miR-132 and miR-146a. Conclusions. The results of the study revealed that miRNA expression, may suggest a possible distinction between healthy women and PCOS patients. miR-132, miR-146a, and miR-222 may have key functions in the pathogenesis of PCOS.
Keywords: Polycystic ovary syndrome; miR-132; miR-146a; miR-222; MICRORNAS; IDENTIFICATION; STEROIDOGENESIS; PROFILE; HEALTH; SERUM; Endocrinology & Metabolism